(untitled) (Journal of Hama University, 2019)
The study was conducted on /30/ of domestic cats with allergic bronchitis to study the effect of some risk factors affecting allergic bronchitis through clinical diagnosis and case history. The study recorded a clinical examination to increase the rate of respiration, where the average was /42/ movement per minute, and an increase in heart rate, where the average was /180/ per minute strike rate, and listening to the voices of the lung study showed 46.6% of the cats that have whistling through the exhale process. As for the effect of some factors affecting the disease of bronchitis allergic, for the type of strain recorded the highest rate of infection in the strains of the type Shirazi by 30% and the lowest in the bred of Himalaya and 6.67%. For the age factor, the study recorded the highest rate of disease in the oldest ages, where 56.67% of the cats studied. For the sex factor, the study recorded the highest percentage of castrated males with 33.33%, followed by sterile females by 30%. As for the exposure to cigarette smoke, the study showed the highest rate of affection in cats that are exposed to cigarette smoke throughout the day and accounted for 50% of the total infected cats.